DEVELOPMENT AND VALIDATION OF AN RP-HPLC METHOD FOR THE ESTIMATION OF SILDENAFIL, FLUOXETINE, AND LOVASTATIN - INDU MELKANI; BIMLESH KUMAR; SHASHI; NARENDRA KUMAR PANDEY (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: Neuropathic pain (NP) arises from trauma to the somatosensory nervous system and can be managed using selective serotonin reuptake inhibitors, such as fluoxetine (FLX) and phosphodiesterase inhibitors, such as sildenafil (SD), and cholesterol-lowering agents such as lovastatin (LOVA). The present study aimed to develop and validate an analytical method for the simultaneous estimation of these drugs (SD, FLX, and LOVA [SFL]) using reverse-phase high-performance liquid chromatography (RP-HPLC). Methods: An RP-HPLC method was developed and validated for the quantification of SFL. Chromatographic separation was achieved using a C-18 reverse-phase ODS column with a mobile phase consisting of acetonitrile and 0.2 M ammonium acetate buffer (55:45) in gradient elution mode. The flow rate was maintained at 1 mL/min, and detection was carried out at 228 nm. The method was validated following the ICH Q2 (R2) guidelines, assessing parameters such as linearity, accuracy, precision, limit of detection (LOD), and limit of quantification (LOQ). Results: The developed method exhibited linearity within the concentration range of 20–100 μg/mL, with a regression coefficient (r2) of 0.9992. Retention times for FLX, SD, and LOVA were recorded at 6.481, 4.238, and 19.778 min, respectively. Recovery studies demonstrated an accuracy range of 94.61–110.44%, with a relative standard deviation of 0.06–2.00%, confirming the precision of the method. The LOD values for FLX, SD, and LOVA were found to be 12.77 μg/mL, 14.81 μg/mL, and 13.28 μg/mL, respectively, while the LOQ values were 45.16 μg/mL, 42.33 μg/mL, and 38.71 μg/mL. Conclusion: The validated RP-HPLC method met all required validation criteria and demonstrated suitability for the accurate quantification of FLX, SD, and LOVA in pharmaceutical formulations. These findings support the potential use of these drugs as an alternative therapeutic strategy for NP.